فاعلية استخدام استراتيجية التفكير البصري الإبداعي في تنمية مهارات الكولاج الفنية لطفل الروضة - رمضان، دينا شوقي عبدالرحمن (جامعة عين شمس - كلية الدراسات العليا للطفولة, 2021)
مقدمة: يتميز التفكير البصري الإبداعي عن سائر عمليات التفكير الأخرى، بأنه الأكثر قدرة على النفاذ إلى عمق الأشياء والظواهر والإحاطة بها وتفسيرها وإدراكها وحفظها، ثم التعبير عنها بصريا. وبالرغم من ذلك نجد أن واقع بعض الروضات يشير إلى أن معلمة الروضة تقوم بتقديم الأنشطة الفنية للطفل قبل أن يكتسب أدنى المهارات اللازمة للقيام بتلك المهام، وقبل أن يكون قادرا عليها، لذلك نجد أن هناك إهمالا كبيرا في تنمية مهارات الكولاج الفنية الروضة، وهذا ما دفع الباحثة إلى السعي وراء تصميم برنامج قائم على استراتيجية التفكير البصري الإبداعي في تنمية مهارات الكولاج الفنية لطفل الروضة. الأهداف "تصميم برنامج باستخدام استراتيجية التفكير البصري الإبداعي لتنمية مهارات الكولاج الفنية لطفل الروضة". الأهمية: البرنامج التدريبي المقترح باستخدام استراتيجية التفكير البصري الإبداعي، واختبار مدى تأثيره في تنمية مهارات الكولاج الفنية لطفل الروضة. المنهج: استخدمت الباحثة المنهج شبه التجريبي، خلال التطبيق العملي لبرنامج الدراسة. العينة: طبقت الدراسة الحالية على عينة قوامها 30 طفلا وطفلة من أطفال الرياض KG2، ثم تم تقسيمهم إلى مجموعتين متكافئتين، قوام كل منهما 15 طفلاً وطفلة، وممن تتراوح أعمارهم الزمانية ما بين (5- 6) سنوات. النتائج: تحققت صحة الفرض الأول حيث تفوق الأطفال الذين تعرضوا للبرنامج التدريبي على مقياس مهارات الكولاج الفنية (أبعاده والدرجة الكلية) في القياس البعدي عنه في القياس القبلي، وتحققت صحة الفرض الثاني حيث تفوق الأطفال الذين تعرضوا للبرنامج التدريبي علي (أطفال المجموعة الضابطة) على مقياس مهارات الكولاج الفنية (أبعاده والدرجة الكلية) في القياس البعدي.
Introduction: The creative visual thinking stands out from other thinking processes for being the most capable one of penetrating into the depth of things and phenomena, covering, explaining, recognizing, and maintaining them, and then expressing them visually. However the reality of some kindergartens indicates that teachers of kindergarten present children with artistic activities before they acquire the needed skills for doing such tasks. Thus, there is a huge negligence in developing the artistic collage skills of kindergarten child. This negligence urged the researcher to design a programme based upon the creative visual thinking strategy to develop the artistic collage skills of kindergarten child. Aims: The current study aimed at designing a programme based upon the creative visual thinking strategy to develop the artistic collage skills of kindergarten child. This main aim could be divided into the following sub- aims: Significance: The significance of the current study could be represented in Hypotheses Of The Study There are statistically significant differences between the mean scores of the children of the experimental group in the pre- and post- scale of the 2- artistic collage skills of kindergarten child ‘its dimensions and the total score’ in favour of the post- scale. Approach: The researcher utilized the quasi- experimental design during performing the practical part of the study. Participants: Participants of the current study included 30 female and male children in KG2. Participants were divided equally in to two groups of 15 children. Results: The first hypothesis was proved as results of children of the experimental group who were exposed to the training programme of the artistic activities in the post- scale of artistic collage skills. The second hypothesis was verified as results of children of the experimental group who were exposed to the training programme of the artistic activities in the post- scale of artistic collage skills.
Keywords: التفكير الإبداعي -- مهارات الكولاج -- مرحلة رياض الأطفال